PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN RELEVANSI DENGAN KEBUTUHAN KONTEMPORER - Silvia Nigrum; Erik Novianto; Willy Radinal (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
The management of Islamic education curriculum that is relevant and adaptive to the challenges of the time is essential in preparing Muslim generations to face the dynamics of modern times. In-depth analysis of inhibiting factors such as lack of technology integration, inadequate emphasis on 21st-century skills, and resistance to change highlights the necessity for transformation in Islamic education. Collaboration from various stakeholders, including educational institutions, teachers, students, parents, and government, is required to address these challenges. Training and professional development for teachers in integrating technology and 21st-century skills are crucial. Policy and cultural changes within Islamic educational institutions are also needed to facilitate curriculum adaptation to changes in time. With these strategic steps, the management of Islamic education curriculum can become more responsive, dynamic, and relevant to the needs of the time and future demands, ensuring that Islamic education remains a source of inspiration, knowledge, and values that bring positive impact to Muslim individuals and society at large